(untitled) (Jurnal Teknologi (Sciences & Engineering), 2019)
Insufficient and various environmental issues of fossil fuels as the current world dominated energy is now becoming a serious global issue. The rapidly increasing demand for alternative energy sources has contributed to the steady growth of renewable energy. Owing to the fact of the abundant presence of palm kernel shell (PKS) as one of palm biomass wastes in South East Asia region, this paper investigates syngas produced from gasified PKS. The investigation is regarding its composition and combustion performance in a gas burner system. It covers emissions analysis, temperature profile and flame length. The produced syngas from downdraft gasifier was burned in the combustion chamber in air-rich and fuel-rich combustion conditions. From the experiment, the results showed that the oxidation zone temperature of above 750°C for the downdraft gasifier is suitable for producing syngas. Produced syngas can be classified as pure-carbon monoxide (CO) syngas due to 94.9% CO content with no hydrogen (H2) content and low heating value (LHV) of 10.7 MJ/kg. The wall temperature profiles for burnt syngas produced via downdraft gasification was higher with longer pattern at fuel-rich condition, which signified higher energy of syngas produced from downdraft gasifier compared to fluidised bed gasifier. The associated flame length was also longer at fuel-rich condition. Produced emission of 56 ppm NOX, 37 ppm CO and 1 ppm SO2 can still be considered as acceptable to human. It can be concluded that syngas produced from PKS shown a high potential to serve as an alternative source of energy due to its high energy content.